When Shopping Becomes Solace: An Analysis of Doom Spending in the Context of Mental Health and Islamic Ethics - Anditasari, Putri; Sabillah, Elza; Budiman, Arip (Philanthropy: Journal of Psychology, 2025)
Doom spending is often conceptualized as a form of mental problem wherein individuals seek temporary relief or satisfaction through impulsive consumption in response to mental distress. This study examines the phenomenon of doom spending within the framework of mental health and Islamic ethical teachings. Employing a qualitative approach, this research adopts a descriptive-analytical method based on a comprehensive literature review of prior studies encompassing psychological, sociocultural, and religious perspectives. Thematic analysis is utilized to identify meaning patterns and explore the correlation between consumptive behavior and Islamic ethical principles. Findings indicate that doom spending not only undermines an individual's financial stability but also aggravates psychological well-being. Islamic teachings emphasize the importance of self-restraint, gratitude (shukr), and detachment from material excess (zuhd). Islam advocates for the pursuit of inner tranquility through worship, self-reflection (muḥāsabah), and responsible financial conduct—reminding individuals that lasting happiness does not stem from fulfilling excessive worldly desires but from spiritual contentment and ethical living.